Protestant Church Affairs in Hungary - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Summary of articles on the Protestant Clergy's peace meeting and elections to the Protestant Council, 10 and 11 July 1957